Strategi Pengembangan Pada Pabrik Roti Sedap Jaya Di Kelurahan Tingkulu Kecamatan Wanea Kota ManadoStrategi Pengembangan Pada Pabrik Roti Sedap Jaya Di Kelurahan Tingkulu Kecamatan Wanea Kota Manado - Paratan, Yersin; Baroleh, Jenny; Porajouw, Oktavianus (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to determine the marketing strategy of existing bread at the Sedap Jaya Bakery Factory. This research was conducted for three months, from April to May 2023. The sampling method was purposive sampling. The data used are primary and secondary. The analytical method used is SWOT analysis.The results showed that based on the SWOT analysis, the results showed that the marketing strategy for Sedap Jaya bread was in quadrant 1, namely taking advantage of strengths and opportunities as well as minimizing weaknesses and preventing threats